2020
DOI: 10.1001/jamanetworkopen.2020.15643
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Prepregnancy Weight and Gestational Weight Gain With Children’s Allergic Diseases

Abstract: Key Points Question Are maternal prepregnancy weight and gestational weight gain associated with childhood allergies? Findings In this cross-sectional study evaluating 8877 children, excessive gestational weight gain was associated with a risk of asthma and/or wheezing, allergic rhinitis, eczema, and food and/or drug allergy, and this risk appeared to be higher when coexisting with maternal prepregnancy overweight or obesity. Low gestational weight gain was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…Similar to previous studies [ 2 , 17 , 19 , 27 29 ], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to previous studies [ 2 , 17 , 19 , 27 29 ], we found that family history of allergy was strongly associated with increased OR of childhood asthma and allergic diseases. Longer breastfeeding duration could reduce these ORs.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, the International Study of Asthma and Allergies in Childhood (ISAAC) phase 3 showed a significant increase in the prevalence of childhood asthma and allergic rhinitis (AR) in most of Asia-Pacific region from 2001 to 2010 [1]. With population and economic growth and urbanization, China has been experiencing a rapid increase in the prevalence of childhood asthma and allergic diseases [2][3][4][5]. These changes have brought heavy economic burdens to individuals, families and the society as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…5 One 2016 study conducted in Ontario found that 44% of toddlers suffered from food allergies, environmental allergies (wheezing, asthma, eczema or rhinitis), atopy or a combination thereof. 6 Though one cross-sectional and several longitudinal studies have assessed the early-life programming of allergic diseases by maternal weight or GWG, they have been limited by small sample sizes (<1000) 7 8 and self-reported measures of the exposure or outcome, [7][8][9][10][11][12][13][14][15][16][17][18][19] which have reduced their generalisability and validity. Further, most have focused on asthma alone, [7][8][9][10][11][12][13][14] none have examined anaphylaxis and none have calculated risk by the length of follow-up time, opting instead for aggregate rates (loglinear model), 8 13 17 odds (logistic model) 7 9-12 14- 16 18 or prevalence ratios (log-binomial model).…”
Section: What This Study Hopes To Add?mentioning
confidence: 99%
“…Further, most have focused on asthma alone, [7][8][9][10][11][12][13][14] none have examined anaphylaxis and none have calculated risk by the length of follow-up time, opting instead for aggregate rates (loglinear model), 8 13 17 odds (logistic model) 7 9-12 14- 16 18 or prevalence ratios (log-binomial model). 19 As well, none of these studies have been undertaken in Canada, which has a unique multicultural population. This proposed research will attempt to address these evidence gaps by carrying out a large population-based study in Canada's most populous province.…”
Section: What This Study Hopes To Add?mentioning
confidence: 99%
“…For instance, the International Study of Asthma and Allergies in Childhood (ISAAC) phase 3 showed a signi cant increase in the prevalence of childhood asthma and allergic rhinitis (AR) in most of Asia-Paci c region from 2001 to 2010 [1]. With population and economic growth and urbanization, China has been experiencing a rapid increase in the prevalence of childhood asthma and allergic diseases [2][3][4][5]. These changes have brought heavy economic burdens to individuals, families and the society as a whole.…”
Section: Introductionmentioning
confidence: 99%